PRAGMATIC ANALYSIS OF DECLARATIVE ILLOCUTIONARY ACTS IN DEDDY CORBUZIER'S PODCASTS - Joko Wibowo; Wahyu Laksono (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2024)
ABSTRACT This research investigates the pragmatic analysis of declarative illocutionary acts in Deddy Corbuzier’s podcast, exploring their use to convey meaning, establish authority, and build trust. Focusing on context and audience reaction, it aims to fill research gaps and enhance understanding of language in digital media, contributing valuable insights to pragmatics and communication studies. This descriptive-qualitative study analyzed declarative illocutionary acts in Deddy Corbuzier’s podcast using J.L. Austin's and John Searle’s Speech Act Theory. Data from selected 2023-2024 episodes and audience reactions were examined, focusing on locution, illocution, and perlocution. Purposive sampling, transcription, and categorization were employed to understand the acts'' functions, with key findings synthesized and presented. This qualitative study analyzed 29 declarative illocutionary acts from Deddy Corbuzier’s podcast, highlighting how statements from Deddy Corbuzier, his guests, and audience reactions convey beliefs and influence perceptions. Using purposive sampling and transcription, the research identified and categorized these acts, revealing their functions and contextual meanings, contributing valuable insights to the understanding of language use in digital media. This research analyzed 29 declarative illocutionary acts in Deddy Corbuzier’s podcast, revealing their impact on public opinion and social realities. It fills a gap in pragmatics by highlighting how these acts shape dialogue in digital media. The study's findings contribute to political discourse analysis, media studies, and sociolinguistics, offering a foundation for future research in diverse media contexts.